Private but not social information validity modulates social conformity bias - Li, Li; Li, King King; Li, Jian (Human brain mapping, 2019)
It is well established that human behaviors are susceptible to others' opinions. However, optimal decision theory mandates choices be made upon the estimated validities of different information sources and little is known about whether and how people could wean themselves off social conformity bias, especially when the social signals are uninformative. Here, we asked subjects to participate in a probabilistic urn guessing task based on their private information as well as observed choices from their partners. Specifically, we manipulated the information validity of these two sources such that only the private evidence was informative. Across trials, social conformity declined, manifested by the increased influence of the private evidence but steady effect of social information. Correspondingly, we found dorsomedial prefrontal cortex (dmPFC) was involved in detecting the conflict of private and social information and conforming to social signal whereas striatum was responsible for selectively updating the influence of private (but not social) evidence contingent on its inferred validity. Furthermore, functional coupling between striatum and dmPFC predicted the resistance toward the influence of social information. Together, these results may provide a mechanistic account of how the conformity bias toward uninformative social information can be remedied.